O02.4 Incidence and duration of pharyngeal and rectal gonorrhea and chlamydia among high-risk men who have sex with men (MSM). (14th July 2019) - Barbee, Lindley; Soge, Olusegun; Haglund, Micaela; Yeung, Winnie; Hughes, James; Khosropour, Christine; Golden, Matthew
Abstract : Background: The duration of untreated extragenital gonococcal (GC) and chlamydial infection (CT) infection is not well defined. Methods: From March 2016 to December 2018, we enrolled 140 MSM in a 12-month cohort study. Men ≥18 years were eligible if they reported receptive anal intercourse and had ≥1 following risks in ≤12 months: 1) diagnosis of GC, CT or syphilis; 2) methamphetamine or poppers use; or 3) >2 sex partners in ≤2 months or >5 in ≤12 months. Enrolled men either tested negative for GC/CT at enrollment, or, tested positive, were treated and waited 2–3 weeks prior to data collection. Each week, men self-collected pharyngeal and rectal specimens and completed an electronic diary. Specimens were tested after study completion (Aptima, Hologic Inc). We defined incident infections as two consecutively positive tests and clearance as > 2 consecutively negative tests. We used Kaplan Meier curves to estimate duration of infection censoring subjects for receipt of pathogen-specific antibiotic, positive swab in final week of study, or loss-to-follow-up. Results: Forty-eight men were observed for 1, 687 weeks and contributed 3, 579 tested specimens. Twenty-four (50%) MSM had ≥1 incident GC/CT infection; 13 (27%) had >1 infection. Overall extragenital GC/CT incidence was 129 (95%CI: 94–172) infections per 100 person-years. Pharyngeal GC, and rectal GC and CT incidence were 35 (95%CI: 20–61), 37 (95%CI: 22–64) and 59 (95%CI: 38–91) per 100 person-years, respectively. 46% (6/13) pharyngeal GC, 43% (6/14) rectal GC, 81% (17/21) rectal CT were censored. The estimated median duration of pharyngeal GC, rectal GC and rectal CT were 15 (95%CI 3 – undefined), 12 (95%CI 2 – undefined) and >20 (95% CI 12 – undefined) weeks. Conclusion: Among high-risk MSM, incident extragenital GC/CT occur frequently: >1 infection per person per year. Untreated, these infections persist for a median of 3 to 5 months. Disclosure: No significant relationships.